New control scheme for synchronization of a photovoltaic system to a three-phase grid to attenuate the harmonics of currents caused by distorted grid voltage - Ismail Boukhechem; Ahcen Boukadoum; Lahcene Boukelkoul; Houssam Eddine Medouce; Rima Lebied (Institute of Advanced Engineering and Science, 2020)
This study presents a new scheme of control for the synchronization ofa photovoltaic (PV) system with a three-phase grid without a line sensor.The approach of the proposed synchronization technique is developed to extract the maximum of PV energy and inject it in the network for various conditions of voltage, and to ensure that the currents injected into the three-phase network emulate the wished sinusoidal forms even when the mains grid voltage is no longer ideal. This paper introduces a new technique of synchronization and elimination of the disturbances created by the distorted tension based on the direct power control without voltage sensors (VF_DPC) with the help of second-order generalized integrator (SOGI) associated with a self-tuning filter (STF) to extract the fundamental virtual flux. The simulation of the proposed system is realized in MATLAB/Simulink environment.